Income convergence and the degree of openess: the case of selected Muslim countries - Duasa, Jarita; Ahmad, Nursilah (2009)
This article examines income convergence or divergence behavior between ten selected OIC (the Organisation of Islamic Conference) economies and the benchmark country of the United States for the period 1970 to 2004. The results are then linked to the degree of openness of the countries under study based on globalization indices. To investigate convergence hypothesis, income differentials between the OIC countries and the benchmark country are computed and a series of test is performed. The tests include Augmented Dickey-Fuller (ADF) stationary linearity test and Kapetanois et al. (KSS) non-linear stationary test. The findings indicate that most of the countries experience income divergence except for three economies. By analyzing the degree of globalization in these economies, it is found that the results support the endogenous theory and dependency approach which predicts that globalization is likely to cause income divergence (inequality) rather than convergence (equality).